Dampak Penerapan Media Pembelajaran Video Tutorial terhadap Hasil Belajar Prakarya Aspek Kerajinan dari Bahan Limbah - Fiwi Enzela; Suib Awrus (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the impact of the application of video tutorial learning media on student learning outcomes in craft learning and entrepreneurship aspects of crafts from waste materials in the form of flat shapes at SMA N 1 Kapur IX District. The technique used in this study was quasi experimental with a pretest-posttest control group design. Data collection was taken from student learning outcomes tests. Data analysis was tested using the Man Whitney u Test in SPSS version 16. The Man Whitney u Test aims to determine whether there is a difference in the average of two unpaired samples. The results of the research show that there is a positive impact on the use of tutorial video learning media on student learning outcomes in craft learning aspects of crafts from waste materials in the form of flat shapes. Therefore. Video tutorial learning media is very good for use in the learning process in order to increase student learning outcomes in craft learning aspects of crafts from waste materials in the form of flat shapes.